CABI Compendium 2022
DOI: 10.1079/cabicompendium.4137
|View full text |Cite
|
Sign up to set email alerts
|

Aleurocanthus woglumi (citrus blackfly)

Abstract: This datasheet on Aleurocanthus woglumi covers Identity, Overview, Distribution, Dispersal, Hosts/Species Affected, Diagnosis, Biology & Ecology, Natural Enemies, Impacts, Prevention/Control, Further Information.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
0
0
Order By: Relevance
“…The response curve showed that the probability of CBF was maximum when the average temperature of the coldest quarter (bio11) is between 15 and 25 • C, falling drastically below or above this range (Figure 3a). These values are in line with the optimum temperature for CBF development, which ranges from 26 to 32 • C [34], but this species can withstand a minimum temperature of up to 14 • C and a maximum of 43 • C [12,35]. However, negative effects are expected when insects are subjected to temperatures close to the minimum and maximum limits they can withstand [36].…”
Section: Discussionmentioning
confidence: 56%
“…The response curve showed that the probability of CBF was maximum when the average temperature of the coldest quarter (bio11) is between 15 and 25 • C, falling drastically below or above this range (Figure 3a). These values are in line with the optimum temperature for CBF development, which ranges from 26 to 32 • C [34], but this species can withstand a minimum temperature of up to 14 • C and a maximum of 43 • C [12,35]. However, negative effects are expected when insects are subjected to temperatures close to the minimum and maximum limits they can withstand [36].…”
Section: Discussionmentioning
confidence: 56%